Refugees’ Encounters With Nordic Rural Areas–Darkness, Wind and “Hygge”! - Herslund, Lise; Paulgaard, Gry (Frontiers in Sociology, 2021)
The paper investigates how refugees settled in rural Norway and Denmark experience and interact with their new rural places of residence. Theoretically, the paper finds inspiration in “phenomenology of practices” (Simonsen, 2012), which emphasises the bodily and sensory experiences of daily life that spur feelings of, for example, “orientation” or “disorientation”. The empirical material is based on fieldwork and qualitative interviews with refugees and local volunteers in 2016/2017/2019 in small towns in the rural north of Norway and rural Denmark. There are several differences between the Norwegian and Danish rural areas, in relation to distances, climate and population density. Nonetheless, the ways in which the rural areas are experienced from within, by refugees settled there, show surprisingly many similarities. Many of the informants, in both the Norwegian and Danish cases, initially expressed frustration at being placed in rural areas without having any say in the matter. Those who were former city-dwellers especially experienced moments of disorientation, as their encounters with Nordic rural life were experienced as the opposite of their urban backgrounds. Limiting structural conditions very much shape the everyday lives of refugees in the first years, when they do not have a car or the financial capacity to find their own house. They feel stressed, with busy everyday lives made up of long commuting hours on public transport. In these first years of uncertainty, the dark and harsh weather very much adds to the feeling of stress and insecurity. What seem to add ‘orientation’ are social relations with other refugees and local volunteers organising activities.